Neurochemical classification of serotonin-immunoreactive neurons co-innervating motor endplates in the mouse esophagus - Zinsser-Krys, Jillena; Kapitza, Christopher; Böhnke, Lena; van der Keylen, Piet; Neuhuber, Winfried; Wörl, Jürgen (Anatomical Record, 2022)
Serotonin immunoreactivity was previously found in myenteric neurons co-innervating motor endplates in the mouse esophagus striated muscle and an involvement in motility control was suggested. However, it is not known if other neuroactive substances are present in these neurons and to what extent they co-localize. First, vasoactive intestinal peptide (VIP) was established as a bona fide marker for putative inhibitory myenteric neurons by evaluating co-localization with neuronal nitric oxide synthase (nNOS) and neuropeptide Y (NPY). Then, co-localization of serotonin and VIP was tested in co-innervating axons on motor endplates, which were visualized with α-bungarotoxin (α-BT) by multilabel immunofluorescence. Myenteric ganglia were also surveyed for co-localization in neuronal perikarya and varicosities. nNOS, NPY, and VIP were completely co-localized in enteric co-innervating nerve terminals on motor endplates. After co-staining with VIP, we found (a) serotonin (5-HT)-positive nerve endings without VIP (44% of 5-HT-positively innervated endplates), (b) 5-HT- and VIP-positive endings without co-localization (35%), and (c) 5-HT- and VIP-positive endings with co-localization (21%). About one-fifth of nerve terminals on motor endplates containing 5-HT originate from putative inhibitory peptidegic nitrergic neurons. However, the majority represents a different population presumably subserving different functions.
CRIS-Team Scopus Importer:2022-07-22
Keywords: 5-hydroxytryptamine; enteric co-innervation; neuromuscular junction; neuronal nitric oxide synthase; neuropeptide Y; vasoactive intestinal peptide